KANKER PAYUDARA SUPPORT GROUPS SEBAGAI UPAYA PENINGKATAN KEPATUHAN TERAPI - Maulida, Mutia Nadra; Muharyani, Putri Widita; Ningsih, Nurna (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Breast cancer survivors need support not only from family, health workers but also from fellow members of the breast cancer survivor community to help breast cancer sufferers in fulfilling their information needs related to their disease and sufferers can determine what treatment decisions they should get to improve therapy compliance and the quality of life of breast cancer patients themselves. This activity aims to examine the problems of breast cancer survivors in a biopsychosocial, spiritual and cultural manner, provide assistance to improve therapy compliance and empower community members who are survivors as supporters in support group activities. The implementation method includes socialization, coaching, empowerment and monitoring and evaluation. This activity was attended by 20 supporters from members of the Association of Supporters of Women with Breast Cancer (P2WPKP) community with 2 stages. The implementation of Phase I includes developing supporter capabilities through socialization, assessment and coaching. The implementation of Phase II includes empowerment and evaluation. The results of this activity are that support groups from fellow breast cancer survivors can help breast cancer survivors to improve therapy compliance.